Clustering of Activity-Related Behaviors in Relation to Self-Reported Causes of Stress among Pre-Adolescents: Results from a National Epidemiological Study - Rena I. Kosti; Thomas Tsiampalis; Matina Kouvari; Ioannis Gketsios; Aikaterini Kanellopoulou; Venetia Notara; George Antonogeorgos; Andrea Paola Rojas-Gil; Ekaterina N. Kornilaki; Areti Lagiou; Demosthenes B. Panagiotakos (Life, 2023)
An epidemiological study was conducted among 1728 10–12-year-old students (55.1% girls) and their parents during 2014–2016 in Greece. This study aimed to identify the dominant clusters of physical activity/sedentariness among preadolescents and investigate their association with self-reported sources of stress. Children’s physical activity levels and sources of stress were evaluated using validated questionnaires that assessed daily hours of activities, both on weekdays and on weekends, including physical activity, screen-based sedentary time, and non-screen-based sedentary time. The k-means algorithm of cluster analysis was applied. Three clusters of children’s physical activity/sedentariness were revealed. Cluster 1 was characterized as “Inactive-Non sedentary”, cluster 2 as “Active –Non-screen sedentary”, and cluster 3 as “Inactive-Sedentary”. Parental needs/expectations were associated with physical activity patterns (p = 0.009), i.e., children assigned to the third and second clusters had 36% and 51% lower odds to be stressed due to parental requirements [(OR for cluster 3 = 0.64, 95% CI = 0.41–0.99), (OR for cluster 2 = 0.49, 95% CI = 0.32–0.76)], compared with their first-cluster counterparts. Considering the need to promote physical activity in early life stages, the identification of these complex activity-related patterns along with their significant interaction with parental expectations as a cause of stress could enhance the effectiveness of targeted behavior change interventions among those parent–child dyads most in need.